Ammonites and Foraminifera of Shiranish Formation (Late Campanian-Maastrichtian) from Sulaimaniya and Erbil Governorates, Northern Iraq - Kamil, Anhar I.; Al-Dulaimi, Salam; Karim, Kamal Haji (Iraqi Journal of Science, 2021)
This study deals with the biostratigraphy of Shiranish Formation (Late Cretaceous), depending on the Ammonite and associated Foraminifera in four outcrop sections, three of which are located in Al-Sulaimaniya governorate (Dokan, Esewa and Kanny dirka sections) and one in Erbil governorate, northern Iraq (Hijran section). Fourteen species of Ammonite belonging to fourteen genera were determined, which are: Dsemoceratidae, Gaudryceras, Gunnarites, Hoplitoplacenticeras, Kitchinites, Kossmaticeratinae, Neancyloceras, Neokossmaticeras, Nostoceras, Paratexanites, Partschiceras, Phylloceras, Pseudophyllites and Yubariceras. Also, thirty- five species of Foraminifera belonging to thirteen genera were determined, which are: Cibicides, Cymopolia, Eggellina, Elphidium, Globigerinelloides, Globotruncana, Hedbergella, Heterohelix, Marginulina, Miliolid, Neobulimmina, Nodosaria and Textularia. Seven range zones were determined, three of which are of Ammonite, which are: Desmophyllites larteti (Seunes, 1892), Nostoceras (Nostoceras) hyatti and Pseudophyllites teres (Van Hoepen, 1920), whereas the others are of Foraminifera species, which are: Glt. gagnebini Tilev, Glt. tricarinata lapparenti Brotzen, Glt. tricarinata tricarinata (Querean) and Glt. Stuartiformis Dalbiez. According to these findings, the age of Shiranish Formation was determined as the Late Campanian- Maastrichtian.